2022
DOI: 10.21608/adjalexu.2021.53782.1138
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Re-Pressing on Biaxial Flexural Strength and Microstructure of Celtra Press (An Invitro Study)

Abstract: INTRODUCTION:Celtra® Press is a zirconia-reinforced lithium silicate (ZLS) glass-ceramic containing 10 % zirconium oxide (ZrO2). This material is used to fabricate dental restorations by pressing technique. After heat pressing procedures leftover buttons are usually discarded. these leftover buttons are suggested to be re-pressed with concerns regarding changes in microstructure and mechanical properties. OBJECTIVES: To evaluate the effects of re-pressing on the mechanical properties and microstructure of Celt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Furthermore, smaller fused crystals appeared (clusters-like) in T2 measuring 1.758µm, which could be due to ZrO 2 which hindered crystal growth. (5,20,21) Although, SEM data revealed that average length of the LDS glass-ceramic (E group) crystals increased after being exposed to (T1) tempering.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, smaller fused crystals appeared (clusters-like) in T2 measuring 1.758µm, which could be due to ZrO 2 which hindered crystal growth. (5,20,21) Although, SEM data revealed that average length of the LDS glass-ceramic (E group) crystals increased after being exposed to (T1) tempering.…”
Section: Discussionmentioning
confidence: 98%